Organizational Citizenship Behaviour (OCB) In Educational Settings: A Narrative Review - Hanson, Janet Lee; Niqab, Muhammad; Arif, Tasleem (JISR management and social sciences & economics, 2022)
Organizational citizenship behaviour (OCB) is a crucial foundation of every human organization. The main purpose of this review paper is to highlight the importance of the OCB in educational settings. Educational institutes have leaders, employees and resources (tangible and intangible). OCB dimensions, in particular: altruism, civic virtue, courtesy, consciousness and sportsmanship, have shown great significance in making associations between employees more powerful thereby improving group performance and influencing positive outcomes of the organization and improvements in school outcomes (as nonprofit service institutions) require the expression of OCB by their employees. Organizational citizenship behaviour (OCB) to stem negative behaviours and enhance positive workplace behaviours. Research has shown the benefits of critically examining the development of OCB in both school leadership and educators. This narrative review of the OCB construct focuses on the role, types, existence of, measurement of, and importance of OCB in educational settings. Implications for the next steps in the process are provided for policymakers, administrators, and teachers to promote OCB in their schools.